1986
DOI: 10.1111/j.1475-097x.1986.tb00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle ammonia and amino acid metabolism during dynamic exercise in man

Abstract: The effect of dynamic exercise on muscle and blood ammonia (NH3) and amino acid contents has been investigated. Eight healthy men cycled at 50% and 97% of maximal oxygen uptake for 10 min and 5.2 min (to fatigue), respectively. Biopsies (quadriceps femoris muscle), arterial and femoral venous blood samples were obtained at rest and during exercise. Muscle NH3 at rest and after submaximal exercise was (means +/- SE) 0.5 +/- 0.1 mmol/kg dry muscle (d.m.) and increased to 4.1 +/- 0.5 mmol/kg d.m. at fatigue (P le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
1
3

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 33 publications
3
91
1
3
Order By: Relevance
“…Cycle ergometer exercise with a load of 70% maximum oxygen uptake (V ・ O2max) for 10 or 20 min increased glutamine and alanine levels, but decreased glutamate levels in muscles 18) . Cycle ergometer exercise with a load of 50% V ・ O2max, followed by a load of 97% of the V ・ O2max for 5.2 min to fatigue, increased alanine levels, but decreased glutamate levels 24) . Furthermore, isometric contraction exercise with two-thirds maximum voluntary contraction to fatigue decreased glutamate levels, but increased alanine and pyruvate levels in muscles 25) .…”
Section: Muscle Fiber Type Differencesmentioning
confidence: 91%
“…Cycle ergometer exercise with a load of 70% maximum oxygen uptake (V ・ O2max) for 10 or 20 min increased glutamine and alanine levels, but decreased glutamate levels in muscles 18) . Cycle ergometer exercise with a load of 50% V ・ O2max, followed by a load of 97% of the V ・ O2max for 5.2 min to fatigue, increased alanine levels, but decreased glutamate levels 24) . Furthermore, isometric contraction exercise with two-thirds maximum voluntary contraction to fatigue decreased glutamate levels, but increased alanine and pyruvate levels in muscles 25) .…”
Section: Muscle Fiber Type Differencesmentioning
confidence: 91%
“…In the present study 1 of the lactate produced was released to the blood during the exercise and the rate of release was as high as 27 mmol min-' for one subject. In ordinary two-legged exercise a rate of lactate entering the blood of 4-7 mmol min-' has been found (Jorfelt, Juhlin-Dannfelt & Karlsson, 1978;Katz et al 1986). Thus, the present data for anaerobic energy yield obtained during exhaustive exercise with a small muscle group in man cannot be extrapolated to the whole body, and values of 100 ml 02 (kg body wt)-1 are likely peak values.…”
Section: Discussionmentioning
confidence: 99%
“…t Spriet, Soderlund, Bergstrdm & Hultman (1987 b); Katz et al (1986). § Svedenhag, Henriksson & Sylven (1983).…”
Section: P6unclassified
See 1 more Smart Citation
“…It has been suggested that the upper limit for lactate efflux is 5 mmol min-' (Jorfeldt, Juhlin-Dannfelt & Karlsson, 1978). However, in more recent studies higher effluxes have been obtained and no saturation was apparent (Katz, Broberg, Sahlin & Wahren, 1986;.…”
Section: Introductionmentioning
confidence: 99%